VP3 Gene Analysis and Histopathological Investigation of Chicken Infectious Anaemia Virus in Poultry Flocks of Andhra Pradesh - Katari, Pavan Kumar; Ramani Pushpa, Rayudu Nandini; Supriya, Racharla Annie; Chowdary Chitturi, Sudha Rani (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Chicken infectious anaemia (CIA) is a significant economic concern affecting poultry, particularly young chicks and is marked by poor  weight gain, anaemia, immunosuppression, and production losses. This research focused on the molecular detection of the VP3 gene,  histopathological examination and phylogenetic analysis of chicken infectious anaemia viruses (CIAVs) in suspected commercial poultry  flocks. Samples were collected from 75 birds across 22 commercial poultry flocks during necropsy. Tissue samples including thymus, bone  marrow, liver and spleen were collected in phosphate buffer saline (PBS) and 10% formalin for molecular detection and histopathological  studies, respectively. Samples were subjected to PCR targeting the VP3 gene producing an amplicon size of 367 bp. Among 22 flocks,  16 were found positive for the VP3 gene. The DNA from four different flocks tested positive, was sequenced and phylogenetic analysis  revealed that all four isolates clustered within the same clade, grouping with strains from diverse regions in India, as well as strains from  China, the USA, Malaysia, and vaccine strains. Histopathological studies revealed moderate degree of lymphocytosis, bone marrow  atrophy, hepatic congestion and periportal fibrosis. The study will enhance the understanding of circulating CIAV genotypes in India  and help in developing effective control and prevention strategies.
Keywords: Chicken infectious anaemia, CIA virus, Histopathology, Phylogenetic analysis, Polymerase chain reaction